CARACTERIZAÇÃO E DESENVOLVIMENTO DE VINAGRES A PARTIR DE MUSCADINIA ROTUNDIFOLIA PRODUZIDOS EM DIFERENTES BIORREATORES - Gusi, Carlos; Schafer De Martini Soares, Fabiana Andreia; Souza, Edson Luiz de (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
Muscadinia rotundifolia is agronomically like vines, but differs due to its rusticity of production, distinct organoleptic characteristics and functional appeal recognized in several scientific works. The constant development of new products is a fundamental factor for the success of the food industry, in this case vinegar is one of them. The objective was to develop Muscadinia rotundifolia grape vinegars with functional and sensorial quality, using different processes. During fermentation at a temperature of approximately 25 ºC, in 3 different processes (Airlift, Orleans and German), samples were collected daily to evaluate the levels of total titratable acidity, volatile acidity, and alcohol kinetic determination. In the Airlift system, at 17 days of fermentation, in the vinegar sample the VA was 2.81%, lower than that required by legislation (4 and 6%) and alcohol 0.4% (maximum 1%). In the German system, at 16 days of fermentation, volatile acidity was 4% and alcohol 1%. In the Orleans system, after 15 days of fermentation, AV was 4.5% and alcohol content 0.5%, as required by law. Under the conditions of the experiment, the Orleans and German systems were efficient in the fermentation of Vitis rotundifolia wine in vinegar, in 15 and 16 days, respectively, and vinegar contents below 1%. In the Airlift system it did not reach the minimum concentration to be considered vinegar by Brazilian legislation.